2021
DOI: 10.2341/17-353-c
|View full text |Cite|
|
Sign up to set email alerts
|

Three-year Clinical Performance of Two Giomer Restorative Materials in Restorations

Abstract: Clinical Relevance The clinical performance of both conventional and flowable giomer restorative materials was particularly good in Class I restorations after three years of service. SUMMARY This study evaluated and compared the clinical performance of a flowable and a conventional giomer restorative material after three years. Forty-four pairs of restorations (total n=88) were placed in Class I cavities with either a flowabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
1
13
1
Order By: Relevance
“…This prospective study investigated and compared the five‐year clinical performance of a flowable and a conventional fluoride‐releasing nano‐hybrid giomer restorative material containing S‐PRG fillers, bonded with a two‐step, self‐etch adhesive during posterior class I restoration. The previous results of this current study had confirmed that both Beautifil II conventional giomer restorative and Beautifil Flow Plus F00 flowable giomer materials were clinically very good in Class I restorations after 3‐year clinical service 24 . Therefore, the null hypothesis tested was that there would be no difference in the clinical performance of the two giomer materials.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…This prospective study investigated and compared the five‐year clinical performance of a flowable and a conventional fluoride‐releasing nano‐hybrid giomer restorative material containing S‐PRG fillers, bonded with a two‐step, self‐etch adhesive during posterior class I restoration. The previous results of this current study had confirmed that both Beautifil II conventional giomer restorative and Beautifil Flow Plus F00 flowable giomer materials were clinically very good in Class I restorations after 3‐year clinical service 24 . Therefore, the null hypothesis tested was that there would be no difference in the clinical performance of the two giomer materials.…”
Section: Introductionsupporting
confidence: 75%
“…While second‐generation giomer restorative materials such as Beautifil II have shown clinically acceptable results for a duration of 36 months, 6,24,25 the existing literature is limited. Therefore, the results of the present study, which indicate that Class I restorations placed with Beautifil II and Beautifil Flow Plus F00 maintain good clinical characteristics after 5 years, contribute significantly to the existing literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluoride release depends on the material's water sorption after placement in the moist environment and is therefore significantly lower than in resin-modified glass-ionomers or compomers [10,19]. Their behavior is considered very similar to resin composite, and their clinical performance is satisfactory [21].…”
Section: Introductionmentioning
confidence: 99%
“…A compromise between satisfactory mechanical properties and the ion-releasing benefits is needed. While mechanical properties of resin composites [18,29,30], glass-ionomers [14,15], and giomers [19,21] are sufficiently explored, studies focused on alkasite materials are scarce and mainly investigate the powder-liquid hand-mixed Cention N [31][32][33][34]. Besides the work of Par and co-workers [4,22,24,25] that focused on ion-releasing properties of Cention, a PubMed search of articles including the capsulated version of Cention resulted in finding only three papers studying fluoride release [35], wear behavior [36], or biologic effects on pulp cells [37].…”
Section: Introductionmentioning
confidence: 99%